2016
DOI: 10.1007/s00520-016-3419-4
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologic events from EGFR inhibitors: the issue of the missing patient voice

Abstract: PurposeAs epidermal growth factor receptor (EGFR) inhibitors are associated with a variety of dermatologic adverse events (dAEs), the purpose of this study was to develop an overview of current knowledge of dAEs associated with EGFR inhibitors and to identify knowledge gaps regarding incidence, treatment, impact on quality of life (QOL), and patient acceptance.MethodA structured literature search was conducted using MEDLINE/PubMed (January 1983 to January 2014). In total, 71 publications published from 2004 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 67 publications
0
44
0
4
Order By: Relevance
“…In our study, pruritus, xerosis and PPE were the most frequent CAE, followed by alopecia and papulopustular rash. Ungual apparatus changes, rash, HFSR, and pigmentary changes were also common [1][2][3][4][5][6][7]35]. In a clinical trial using EGFRI, Joshi et al reported that the most common skin toxicities were rash, xerosis, paronychia, and pruritus [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, pruritus, xerosis and PPE were the most frequent CAE, followed by alopecia and papulopustular rash. Ungual apparatus changes, rash, HFSR, and pigmentary changes were also common [1][2][3][4][5][6][7]35]. In a clinical trial using EGFRI, Joshi et al reported that the most common skin toxicities were rash, xerosis, paronychia, and pruritus [30].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that new agents, including targeted therapies, offer better disease control and survival rates compared to classical cytotoxic chemotherapies. [1][2][3][4][5][6]. Concurrently, new drugs usually mean new adverse event pro les, including cutaneous adverse events (CAEs) [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Cutaneous and mucosal reactions are dominant side effects, which can usually be managed easily [5]. However, 45-100% of patients acquire an acneiform rash, and only a minority develops dermatitis or higher-grade skin toxicities, but little is known about the impact this may have on the individual [6]. The onset is typically a few days after therapy, with a peak about 2 weeks after.…”
Section: Discussionmentioning
confidence: 99%
“…Immunogenic effects of anti-EGFR mAbs interfering with ADCC in bacterial defense could be considered beyond the well-known antiproliferative effects of EGFR inhibitors on non-mutated tissue. Moreover, the patient's burden as well as the economic burden even of non-life-threatening side effects may be considerable [6,19]. …”
Section: Discussionmentioning
confidence: 99%
“…Unlike some targeted therapies used for other types of cancer (eg, sorafenib, imatinib), which can cause multiple cutaneous AEs (eg, hypopigmentation, maculopapular rash, epidermoid cysts) [31,32], hedgehog signaling pathway inhibitors primarily produce alopecia as a cutaneous AE [32]. Common noncutaneous AEs from hedgehog inhibitors include muscle spasm, dysgeusia, fatigue, and nausea [20,23].…”
Section: Discussionmentioning
confidence: 99%